Indian Spectacle : College Mascots and the Anxiety of Modern America - Guiliano, Jennifer (Book collections on Project MUSE., 2015)
"In recent decades U.S. colleges and universities have been prone to changing athletic conference affiliations, seeking increased public prestige, building fan bases, and, of course, growing revenues. Such moves are driven by a very realistic set of calculations: in 2010 the collective revenue of the fifteen highest-grossing teams in Division I of the National Collegiate Athletic Association (NCAA) topped one billion dollars, a hefty figure that does not even take into account the revenue generated by the sales of university-related apparel and athletic gear. Expressions of team allegiance, particularly the display of sports mascots, are a visual expression of this American obsession with collegiate sport. In American Spectacle, historian Jennifer Guiliano investigates the role of sports mascots in the big business of American college football in order to connect mascotry to twentieth-century expressions of community identity, individual belonging, stereotyped imagery, and cultural hegemony. To do so, she historicizes the creation and spread of mascots and university identities as something bound up in the spectacle of halftime performance, the growth of collegiate competition, the anxiety of middle-class masculinity, and the commercialization of athletics in the first two decades of the twentieth century"--